2021
DOI: 10.1016/j.asmr.2021.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Both Open and Arthroscopic Latarjet Result in Excellent Outcomes and Low Recurrence Rates for Anterior Shoulder Instability

Abstract: Purpose The purpose of this study is to evaluate the patient-reported outcomes of open Latarjet (OL) compared to arthroscopic Latarjet (AL) for anterior shoulder instability. Methods A retrospective review of patients who underwent either OL or AL for anterior shoulder instability between 2011 and 2019 was performed. Recurrent instability, visual analog scale (VAS) score, Shoulder Instability-Return to Sport after Injury (SIRSI), Subjective Shoulder Value (SSV), Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…There was no statistically significant difference in external rotation between the procedures at the last follow-up (MD, 6.23; 95% CI, -2.47 to 14.93; P ¼ . 16).…”
Section: Results Of Meta-analysesmentioning
confidence: 99%
“…There was no statistically significant difference in external rotation between the procedures at the last follow-up (MD, 6.23; 95% CI, -2.47 to 14.93; P ¼ . 16).…”
Section: Results Of Meta-analysesmentioning
confidence: 99%
“…Of the 37 included datasets, complication rates were reported in 15 (arthroscopic bony Bankart repair, n = 3; arthroscopic Latarjet, n = 12), of which 3 reported rates instead of absolute values [23, 57]. There was no statistical difference in complication rate following arthroscopic bony Bankart repair (0.01; CI 0.00–0.07; I 2 = 0%) compared to arthroscopic Latarjet (0.03; CI 0.00–0.06; I 2 = 47%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A further 87 studies were excluded after full‐text review. This left 29 eligible studies [1, 7, 8, 11, 14, 16–18, 23, 24, 29–32, 38, 40–45, 47, 48, 53, 55–59] of which 16 assessed arthroscopic bony Bankart repair, 13 assessed arthroscopic Latarjet (Tables 1 and 2). All studies reported preoperative glenoid bone loss: 21 reported mean preoperative glenoid bone loss, of which 4 created subgroups of glenoid bone loss and reported the mean loss of each subgroup, while 8 used a threshold of glenoid bone loss as a part of their inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…W e know that a bone block augmentation procedure (e.g., distal tibial allograft/Latarjet) provides excellent results for those patients with recurrent shoulder instability and critical glenoid bone loss. [1][2][3][4][5][6] We also know that the addition of a remplissage procedure to a Bankart repair provides good results for those unstable shoulders with an engaging Hill-Sachs or offtrack lesion. [7][8][9][10] But what about those patients with critical bipolar bone loss.…”
Section: See Related Article On Page 2609mentioning
confidence: 99%